The effectiveness of posters as a learning media to improve student learning quality - Harsono, Harsono; Rosanti, Susi Yulia; Abu Seman, Noor Aslinda (Academic Research Publishing Group, 2019)
The aim of the study is to identify the importance of poster as a learning media that can be utilized in learning activities. It also aims to explore the learning outcomes of students who use poster as learning media. In Indonesia, high school students are not allowed to carry a mobile phone, while the school on the other hand, does not provide enough computers for all students. The school computer laboratory could only cater for students need interchangeably. Therefore, teachers in schools choose other media that they think are effective, such as poster media. The poster media was seemed very relevant and appropriate to improve the quality of learning and student achievement. This study involved both qualitative and quantitative research method through Four-D model (Define, Design, Development, and Dissemination) that used for the learning material development. The data was collected through interview with two experts and experimental research design among two groups of students. The qualitative data were analyzed and the experimental data was tested using T-test statistical analysis. The learning outcomes with poster as learning media showed the mean values of the control and experimental groups were, respectively, 60.97 and 85.86. It indicated the difference in learning outcomes of 24.89. The produced poster was also assessed by media experts and curriculum experts. This study recommended that poster is very feasible and relevant to be utilized as a form of learning media in improving quality of learning and engagement with students.